Pengaruh Pola Asuh Orang Tua terhadap Hasil Belajar Siswa Setingkat Menengah Atas - Mohammad Fajar Shodiq; Nur Aniqa Pernaningtik; Erni Wijayanti; Nur Nabila Ilma Nafisa; Didit Darmawan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The purpose of this study was to examine the impact of parenting patterns on student learning outcomes, especially in terms of increasing students' enthusiasm, independence, and interest in learning activities. This study focuses on parental involvement in supporting student learning activities at home and its impact on academic achievement. By identifying the types of parenting patterns and their impacts, it is hoped that this study can provide useful understanding for parents, educators, and schools to build constructive cooperation between families and educational institutions. This study uses a qualitative method through a literature review approach. The data used comes from trusted databases such as Google Scholar, Web of Science, and Scopus which are sources of information in the form of articles, journals, books, and other scientific publications. The literature reviewed was selected based on the following criteria: published in the last 10 years and discusses the impact of parenting patterns on student learning outcomes. The findings of this study reveal that parenting patterns are a key factor in determining learning outcomes. Supportive and participatory parenting patterns shape positive attitudes, high motivation, and learning responsibilities in children. Active parental involvement is a major element in students' academic success.